Probiotic supplementation reduces the duration and incidence of infections but not severity in elite rugby union players - Haywood, B. A.; Black, K. E.; Baker, D.; McGarvey, J.; Healey, P.; Brown, R. C. (Journal of Science and Medicine in Sport, 2014)
Objectives: The attenuation of the number and severity of infections is of importance to athletes. Probiotics use has increased over recent years with beneficial effects believed to include improvements in immune function. Research has focused on their effectiveness for reducing the number, duration and severity of infections amongst endurance athletes. At present no research has been undertaken with team sport athletes. This randomised controlled trial aimed to determine the effectiveness of probiotics on the number, duration and severity of infections amongst elite union rugby players. Design: Randomised control trial with two arms; placebo and probiotic. Methods: Thirty elite rugby union players were allocated in random order to receive a probiotics supplement or a placebo for four weeks each. Supplements were consumed on a daily basis. There was a four week washout period between treatments. Participants completed a daily diary to identify and rate the severity of any infectious symptoms. Results: During the probiotic treatment 14/30 participants never experienced a single upper respiratory tract illness (URTI) or gastrointestinal (GI) episode, compared to 6/30 on the placebo supplementation (p = 0.033). The mean ± standard deviation for the number of days of illness tended to be higher for the placebo, (5.8 ± 6.6 days) than probiotic (3.4 ± 4.6 days), (p = 0.054). There was no significant difference in the severity of the symptoms between the two treatment groups (p = 0.110). Conclusions: These positive effects of probiotic supplements provide evidence for the beneficial effects of daily supplementation with these probiotic strains in highly trained rugby union players.